N-(2-Hydroxyethyl)-L-valyl-L-leucine in rat urine as a hydrolytic cleavage product of ethylene oxide adduct with globin - Mráz, Jaroslav; Hanzlíková, Iveta; Linhart, Igor; Dušková, Šárka; Dabrowská, Ludmila; Hejl, Kamil (Archives of toxicology, 2019)
Ethylene oxide (EO), a genotoxic industrial chemical and sterilant, forms covalent adducts with DNA and also with nucleophilic amino acids in proteins. The adduct with N-terminal valine in globin [N-(2-hydroxyethyl)valine (HEV)] has been used in biomonitoring of cumulative exposures to EO. Here we studied in rats the fate of EO-adducted N-termini of globin after life termination of the erythrocytes. Rat erythrocytes were incubated with EO to produce the HEV levels in globin at 0.4-13.2 µmol/g as determined after acidic hydrolysis. Alternative hydrolysis of the isolated globin with enzyme pronase afforded N-(2-hydroxyethyl)-L-valyl-L-leucine (HEVL) and N-(2-hydroxyethyl)-L-valyl-L-histidine (HEVH), the EO-adducted N-terminal dipeptides of rat globin α- and β-chains, respectively. The ratio of HEVL/HEVH (1:3) reflected higher reactivity of EO with the β-chain. The EO-modified erythrocytes were then given intravenously to the recipient rats. HEVL and HEVH were found to be the ultimate cleavage products excreted in the rat urine. Finally, rats were dosed intraperitoneally with EO, 50 mg/kg. Herein, the initial level of globin-bound HEVL (11.7 ± 1.3 nmol/g) decreased almost linearly over 60 days corresponding to the life span of rat erythrocytes. Daily urinary excretion of HEVL was almost constant for 30-40 days, decreasing faster in the subsequent phase of elimination. Recoveries of the total urinary HEVL from its globin-bound form were 84 ± 6% and 101 ± 17% after administrations of EO and the EO-modified erythrocytes, respectively. In conclusion, urinary HEVL appears to be a promising novel non-invasive biomarker of human exposures to EO.
Keywords: Animals; Ethylene Oxide; Valine; ethylenoxid; biologické markery; hydrolýza; Biomarkers; monitorování životního prostředí; erytrocyty; Hazardous Substances; dipeptidy; Dipeptides; Leucine; globiny; valin; Erythrocytes; leucin; Hydrolysis; Globins; Environmental Monitoring; krysa rodu Rattus; nebezpečné látky; zvířata; Rats